The Application of PBL Assisted by Wordwall on Learners' Interest at SMP Negeri 7 Kisaran - Nasution, Tri Purnama; Sambayu, Harry; Noviyanti , Rini (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research explores the application of PBL integrated into a game-based digital platform namely Wordwall to enhance learners’ interest in learning English. Initial findings from class VIII-6 at SMP Negeri 7 Kisaran showed that learners demonstrated very poor interest, with a pre-cycle score of only 18.75%. Learners expressed the need for more interactive and engaging learning experiences, particularly through games. The study employed Classroom Action Research (CAR) over two cycles, each consisting of planning, action, observation, and reflection. The data in this study were collected by using questionnaires. Four indicators were used to assess interest: attention, interest, excitement, and involvement. The result of this study revealed a consistent increase in learners’ interest across both cycles. In Cycle 1, scores rose from 44.53% in the first meeting to 52.34% in the second meeting. In Cycle 2, interest further increased to 71.87% and 87.5%, reaching the “very high” category. The highest improvements were seen in attention and involvement, indicating that learners became more focused and active during lessons. This study concludes that integrating PBL into Wordwall significantly boosts learners’ interest and engagement in English. It supports the idea that digital, game-based tools can enhance classroom participation and help address low interest among learners.